(Concession and contrast) clauses in classic and modern Arabic - حازم كيان أحمد (Al-Adab Journal, 2019)
Certainly both single words and clauses are very important, but whereas treating single words and mistakes concerning them is widely spread, little care is spent to clauses and what they are exposed to in different uses and contexts though they may be more important because of their vagueness and delicacy. Therefore, I intended to contribute in illustrating the different uses of (concession and contrast) clauses in modern Arabic. This paper is divided into two sections, preceded by an introduction and followed by a conclusion and a bibliography of references. The first section is about different forms of (concession and contrast) clauses in classic Arabic, and the second sheds light on modern linguistic uses of (concession and contrast) clauses, and explores the differences we find between modern uses of these clauses and ancient uses of them.